Effects of 12-week combined training versus high intensity interval training on cardiorespiratory fitness, body composition and fat metabolism in obese male adults - Mattia D'Alleva; Filippo Vaccari; Francesco Graniero; Nicola Giovanelli; Mirco Floreani; Federica Fiori; Michela Marinoni; Maria Parpinel; Stefano Lazzer (Elsevier, 2023)
Background/Objectives: A weekly combination of a high volume of moderate-intensity continuous training (MICT) with a low volume of high-intensity interval training (HIIT) provides important improvements in body composition and physical capacities in individuals with obesity. However, previous studies did not determine the weekly proportions of HIIT and MICT a priori. This study aimed to investigate changes in body composition, physical capacities and the fat oxidation rate in obese male adults by comparing a combination of MICT and HIIT, called combined training (COMB), with HIIT for a 12-week period. Methods: Thirty-four obese male adults (mean age: 39.4 ± 7.0 y; mean body mass index [BMI] 34.0 ± 4.2 kg·m−2) participated in this study (n = 18 for COMB, n = 16 HIIT), attending ∼ 36 training sessions. The COMB group performed 3 repetitions of 2 min at 95% of peak oxygen uptake (V'O2 peak) (e.g., HIIT ≤20%), followed by 30 min at 60% of VO2 peak (e.g., MICT ≥80%). The HIIT group performed 5-7 repetitions of 2 min at 95% of VO2 peak. At baseline (PRE) and at the end of the training period (POST), body composition, VO2 peak, and the fat oxidation rate were measured. The two training programs were equivalent in caloric expenditure. Results: At POST, body mass (BM) and fat mass (FM) decreased by a mean of 3.09 ± 3.21 kg and 3.90 ± 2.40 kg, respectively (P < 0.05), in both groups and V'O2 peak increased in both groups by a mean of 0.47 ± 0.34 L·min−1 (P < 0.05). The maximal fat oxidation rate increased similarly in both groups from 0.32 ± 0.05 to 0.36 ± 0.06 g·min−1 (P < 0.05). Conclusion: COMB training represents a viable alternative to HIIT to improve anthropometric characteristics, physical capacities and fat oxidation in obese male adults.